Evaluasi Misfit-Score Strategi Pemanufakturan dengan Strategi Bisnis Serta Dampaknya pada Kinerja Operasional - Titik Kusmantini (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
This research was established based on organizational kesesuaian hubungan theory, where in the formulation of strategic decision in manufacturing strategic must be alingment with business strategy. The higher congcruence can create higher performance. The hypothesis was tested with multiple regression models and the degree of fit (misfit-score) to computing with euclidean distance as regression coeficient.Keyword: Manufacturing, Business, Performance, Misfit-Score.